Portaria PRES nº 150, de 15 de julho de 2021 - Edmar Gomes Machado (DOU, Brasília, DF, 19 jul. 2021. Seção 2, p. 49., 2021)
Nomeia Wender Pontes Fagundes para o cargo em comissão de Assessor Nível II.